A Community-Based Participatory Research Project Involving Latino Families of Deaf and Hard-of-hearing Children - Tanya L. Flores (The University of Alabama, 2022)
The community-based participatory research project described in this paper was designed to help Spanish-speaking families of deaf and hard-of-hearing children gain access to necessary health, education, and local resource information. The project was motivated by the need to improve communication between medical and education resource centers with Spanish-speaking families. This paper reports on the specific methods and implementation of the partnership approach, the development of the project, and lessons learned for future projects of this type.